Methods of economic impact assessment - Rushton, Jonathan; Thornton, Philip K.; Otte, M.J. (1999)
A broad framework for the assessment of the economic impact of animal diseases and control of these diseases is described. Various levels of analysis are discussed, from the herd, to the household, the sector, the nation and the region. For each of these levels, methods of economic impact assessment are outlined and discussed with respect to the objectives, data requirements and outputs of each type of assessment. In addition, the authors attempt to describe the conditions under which the various methods might be used. To conclude, a discussion of the state of the art is presented, and areas of further research are identified.